Early evidence of SARS-CoV-2 in Milan, Jan-Feb 2020 - Gregorio P. Milani; Giovanni Casazza; Antonio Corsello; Paola Marchisio; Alessia Rocchi; Giulia Colombo; Carlo Agostoni; Giorgio Costantino (BMC, 2021)
Abstract Background A few studies have suggested that the Severe Acute Respiratory Syndrome coronavirus 2 (SARS-CoV-2) was present in Northern Italy several weeks before its official detection on February 21, 2020. On the other hand, no clinical data have been provided so far to support such hypothesis. We investigated clinical-epidemiological evidence of SARS-CoV-2 infection among children and adults referring to emergency department (ED) in the main hospital of the center of Milan (Italy) before February 21, 2020. Methods A retrospective analysis of medical records of ED visits at the Fondazione Ca' Granda Policlinico, Milan between January 11 and February 15 in 2017, 2018, 2019 and in 2020 was performed. The number of subjects referring with fever, cough or dyspnea was compared between the studied period of 2020 and the previous 3 years, by calculating a standardized referral ratio (SRR, number of observed cases in 2020 divided by the number of expected cases according to 2017-2019) and the corresponding 95% confidence interval (CI). Results In the pediatric ED, 7709 (average 2570/year) and 2736 patients were visited during the period 2017-2019 and in the 2020, respectively. Among adults, 13,465 (average 4488/year) and 4787 were visited during the period 2017-2019 and in the 2020, respectively. The SRR was 1.16 (95% CI 1.10-1.23) in children and 1.25 (95% CI 1.16-1.35) in adults. The ratio for the two (children and adults) SRRs was 0.93 (0.84-1.02), suggesting a trend towards a higher frequency in adults compared to children. Conclusions This study suggests that SARS-CoV-2 might have spread in Milan before February 21, 2020 with a minor trend among children.